#Crime Social Media, Crime, and the Criminal Legal System - Hayes, Rebecca M. (Palgrave Studies in Crime, Media and Culture, 2018)
As research continues to accumulate on the connections between media and crime, #Crime explores the impact of social media on the criminal legal system. It examines how media influences our perceptions of crime, the perpetration of crime, and the implementation of punishment, whilst emphasizing the significance of race, ethnicity, class, gender, and sexuality. It offers an accessible and in-depth examination of media and in each chapter there are case studies and examples from both legacy and new media, including discussions from Twitter that are being used to raise awareness of criminal legal issues. It also includes interviews with international scholars and practitioners from Australia, Belgium, and the United States to voice a range of global perspectives. This book speaks broadly to those interested in criminology, criminal justice, media and culture, sociology, and gender studies.